Influência do espaçamento na produtividade de sementes de malva (Urena lobata L.) em terra firme no Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2015)
The Malva (Urena lobata L.) is currently the main species used for natural fiber production in the Amazonas State. However, seed supply remains a strategic and critical issue to the production chain of the fiber. Due to total lack of local production of seeds, Amazonas fiber producers depend on acquisition by the state govern of about 100 tons of seeds produced in other regions, each year. Thus become necessary studies to determine technical recommendations for the implementation of seed production systems adapted to local conditions, for the state to become self-sufficient in the supply of this raw material. This study aimed to evaluate the effect of different spacing on productivity of Malva plants for seed production. The experiment was conducted at the Experimental Farm of Federal University of Amazonas – UFAM, in Manaus. The experimental design was completely randomized with three treatments corresponding to the spacing of (T1) 1.0 x 1.0m, (T2) 1.5 x 0.5m (T3) 1.0 x 0.5 m with 10 repetitions, each repetition corresponding to the average of four plants. The following characteristics were evaluated: plant height, stem diameter, number of branches, number of flowers, number of green fruits and number of ripe fruit, the seed production and dry weight of plants. The results were submitted to analysis of variance by F test at 5% probability. For the phenological parameters, 1,5 x 0,5 was higher in stem diameter, fresh fruits and ripe fruit. The treatments 1,5 x 0,5 was also statistically superior for the variable of production of seed. It was concluded that for the establishment of U. lobata L. seed production systems in Amazonas, it is recommended to use 1.5 x 0.5m spacing, in which can be obtained about 1,700 kg of seed per hectare.
Keywords: Fenologia; Malvácea; Produção de semente; Urena lobata L; Phenology; Seed production; CIÊNCIAS AGRÁRIAS: AGRONOMIA